Genetic diversity of Prunus necrotic ringspot virus infecting stone fruit trees grown at seven regions in China and differentiation of three phylogroups by multiplex RT-PCR. (August 2015) - Cui, H.G.; Liu, H.Z.; Chen, J.; Zhou, J.F.; Qu, L.N.; Su, J.M.; Wang, G.P.; Hong, N.
Abstract: Prunus necrotic ringspot virus (PNRSV) is an important pathogen of stone fruit trees ( Prunus sp.) worldwide. In this study, 35 out of 166 (21.1%) samples of Prunus sp. randomly collected from seven regions in China were tested to be positive for PNRSV by reverse transcription-polymerase chain reaction (RT-PCR). The coat protein (CP) gene of 28 isolates and movement protein (MP) gene of 15 isolates shared 87.1–100% and 82.9–99.9% nucleotide sequence identity, respectively. Phylogenetic analyses of CP and MP gene sequences revealed three well-defined phylogroups represented by isolates PV96, PV32 and PE5, with distribution frequencies of 37.5%, 56.3% and 6.3%, respectively. Sequence variations around a hexanucleotide insertion at sites 124–129 in the CP gene in six PV32-type isolates from Prunus avium resulted in an alteration of secondary structure. A multiplex RT-PCR assay based on CP gene sequences was developed to differentiate isolates in three phylogroups. Highlights: Prunus necrotic ringspot virus was identified from seven Prunus species in China by RT-PCR. The CP gene of 28 isolates and MP gene of 15 isolates were sequenced. A multiplex RT-PCR assay based on CP gene sequences was developed to differentiate isolates in the three phylogroups.